MULTI-STAKEHOLDER VARIETAL INNOVATION PLATFORMS. A SOCIOTECHNICAL PARTNERSHIP RESEARCH SCHEME ASSESSED IN BENIN - (:unkn) unknown (My University, 2010)
Participatory plant breeding research may be hampered by the fact that results that have been obtained in very specific localized settings cannot be disseminated and scaled. Varietal innovation platforms aim to overcome this problem by ensuring that the viewpoints of people involved in assessments are representative of broad interest groups and that assessment results will be validated and disseminated by an organization. Each platform is designed as a sociotechnical scheme consisting of a five-member steering committee (SC), a club with a membership of 25 local users and experts (CLUE), a common varietal test plot and a network of around 15-20 on-farm plots. The aim is to describe, evaluate and disseminate improved varieties to target groups of stakeholders faced with the same environmental, agricultural and socioeconomic constraints. Partnerships between all of these stakeholders are set up, organized and managed according to six principles outlined in a charter—legitimacy, competence, efficiency, democracy, solidarity and transparency. Two experimental platforms were set up in the villages of Zé and Tori-Bossito, in southern Benin, to assess plantain varieties released by the Centre africain de recherche sur le bananier et le plantain (CARBAP). These platforms were monitored 20 months following their creation. The survey showed that the two platforms had successfully carried out all of their initially planned activities. The CLUEs identified four interesting varieties. The survey focused on the future plans made by SC and CLUE members to tap the benefits of knowledge acquired during 18 months. It showed that: (i) their plans provided conditions favorable for varietal dissemination and scaling, (ii) SC plans were based on transfer of the platform scheme whereas the CLUE plans were based on varietal dissemination, and (iii) the Tori plan was collective while the Zé plan was more individually focused. Our analysis highlighted that the respect of th
Keywords: African Research